An expert system for assessing the technical and economic risk of pipe rehabilitation options. Issue 22 (1st December 2015) - Marlow, D.; Gould, S.; Lane, B.
Highlights: Investment in ageing infrastructure is a significant societal challenge. Cast iron pipes still constitute a significant portion of many water networks and various technologies are available to rehabilitate them. Under certain circumstances, trenchless renovation can be considered a prudent option, as can the use of trenchless replacement. Diffusion of such innovations in the USA is lagging in comparison to other countries. An expert system has thus been developed to facilitate asset managers to make risk appropriate selection of rehabilitation technologies. Abstract: Cast iron (CI) pipes still make up a significant portion of many water distribution systems across the globe. A range of trenched and trenchless technologies are available to rehabilitate these pipes, but in the USA trenched replacement is still the standard approach used, despite 'trenchless' options having significant financial, social and environmental benefits. This paper focuses on the development of a decision support tool to help asset managers determine which rehabilitation technique to select, with specific emphasis given to whether to renovate or replace a group of CI pipes. The tool encapsulates expert knowledge on a range of issues, and provides an assessment of both the practical and economic feasibility of available techniques. During the tool development, it was recognized that the economic justification for renovation depended strongly on the assumed operational life of the renovated asset, which is inherently uncertain. To circumvent this, the tool calculates the minimum required service life (MRSL) for technically feasible renovation options, taking into account the life cycle costs of rehabilitation scenarios. The MRSL is the operational life beyond which renovated assets provide economic benefit in comparison to replacement options. This metric thus allows asset managers to determine if the risk of renovating pipes is worth taking when considered in light of the potential cost savings and other benefits. Overall, the tool is intended to encourage innovation diffusion in the USA and to help utilities adopt a 'risk appropriate' approach to pipe rehabilitation.